Barriers to Providing VTE Chemoprophylaxis to Hospitalized Patients: A Nursing‐Focused Qualitative Evaluation. Issue 11 (21st August 2019) - Kreutzer, Lindsey; Yang, Anthony D; Sansone, Christina; Minami, Christina; Saadat, Lily; Bilimoria, Karl Y; Johnson, Julie K
Abstract : BACKGROUND: Venous thromboembolism (VTE) is a serious medical condition that results in preventable morbidity and mortality. OBJECTIVES: The objective of this study was to identify nursing‐related barriers to administration of VTE chemoprophylaxis to hospitalized patients. DESIGN: This was a qualitative study including nurses from five inpatient units at one hospital. METHODS: Observations were conducted on five units to gain insight into the process for administering chemoprophylaxis. Focus group interviews were conducted with nurses and were audio‐recorded, transcribed verbatim, and analyzed using the Theoretical Domains Framework to identify barriers to providing VTE chemoprophylaxis. RESULTS: We conducted 14 focus group interviews with nurses from five inpatient units to assess nurses' perceptions of barriers to administration of VTE chemoprophylaxis. The barriers identified included nurses' misconceptions that ambulating patients did not require chemoprophylaxis, nurses' uncertainty when counseling patients on the importance of chemoprophylaxis, and a lack of comparative data for nurses regarding their specific refusal rates. CONCLUSIONS: Multiple factors act as barriers to patients receiving VTE chemoprophylaxis. These barriers are often modifiable targets for quality improvement. There is a need to focus on behavior changes that will remove or minimize barriers and equip nurses to ensure administration of VTE chemoprophylaxis by engaging patients in their care.